Quantitative assessment of the effect of subclavian steal syndrome on left anterior descending artery flow - Hasan Arı; Selma Arı; Sencer Camcı; Alper Karakuş; Mehmet Melek (KARE Publishing, 2017)
We presented a case of subclavian steal syndrome which has been evaluated and treated quantitatively by using fractional flow reserve technique. Treatment strategy to resolve symptoms of angina in patients with steal syndrome is controversial. Quantitative evaluation should direct choice of treatment strategy.